A Critique on the Book Ethnicity and Ethnocentrism in Iran: Myth and Reality - Siavash Gholipour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book Ethnicity and Ethnocentrism: Myth and Reality is a narrative about the conflicts of ethnic groups in Iran after the First World War until the last decades of the 14th century. According to the author, ethnicity and ethnic groups are modern categories and have no history in Iran. The three factors of the centralist and authoritarian state, the utilitarianism of the elites and the international forces played a role in the emergence of these conflicts and the formation of ethnicity. The book examines ethnicity and ethnocentrism in the context of internal and external political and social relations; It also shows the constructiveness of ethnic nationalism based on abundant historical data. In line with the book's themes, the author introduces inclusive government, highlighting cultural commonalities, and de-escalation policies as appropriate strategies for dealing with Iran's multicultural situation. There are criticisms of this work that can be mentioned as follows: the book has used different approaches without combining them and lacks paradigm coherence; Like positivists, it seeks a criterion for determining the boundaries of ethnicity, but there is no such criterion; All the arguments of the book in the direction of the construction of ethnicity are also applicable to national identity, but the author is silent about this and falls into a kind of national essentialism; It downplays the role of economic policies and development plans in ethnic conflicts; Finally, it neglects the impact of modern social change and the inevitable presence of the "other" in the formation of ethnicity.